2006
DOI: 10.1016/j.micron.2005.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy of Bacillus spore surface morphology

Abstract: Bacillus spore surface morphology was imaged with atomic force microscopy (AFM) to determine if characteristic surface features could be used to distinguish between four closely related species; Bacillus anthracis Sterne strain, Bacillus thuringiensis var. kurstaki, Bacillus cereus strain 569, and Bacillus globigii var. niger. AFM surface height images showed an irregular topography across the curved upper surface of the spores. Phase images showed a superficial grain structure with different levels of phase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 36 publications
2
25
2
Order By: Relevance
“…The majority of spores from the ⌬Sterne strain ( Fig. 2A) exhibited a smooth raisin-like surface with characteristic ridges similar to those observed by atomic force microscopy (10,48). Many of the bclB-negative spores displayed a rougher, dimpled appearance (Fig.…”
Section: Resultssupporting
confidence: 59%
“…The majority of spores from the ⌬Sterne strain ( Fig. 2A) exhibited a smooth raisin-like surface with characteristic ridges similar to those observed by atomic force microscopy (10,48). Many of the bclB-negative spores displayed a rougher, dimpled appearance (Fig.…”
Section: Resultssupporting
confidence: 59%
“…AFM images revealed previously unrecognized germination-induced alterations in spore coat architecture and in the disassembly of outer spore coat rodlet structures. These and other studies (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), including our previous work that showed that the spores of four closely related Bacillus species can be distinguished by AFM surface morphology analysis (37) have proved AFM to be a powerful tool complementary to EM techniques, providing three-dimensional images of native, minimally processed biological samples with nanometer resolution.…”
mentioning
confidence: 74%
“…The surface of Bacillus subtilis and Bacillus anthracis spores is populated by ridge structures largely oriented with the long axis of the spore. We previously showed that four closely related species of Bacillus spores can be distinguished by surface morphology analysis (54). Using thermal atomic force microscopy (AFM), we recently characterized thermal effects on the topographic morphology and nanomechanical properties of Bacillus anthracis spores at elevated temperatures (55,56).…”
mentioning
confidence: 99%